Kenya Elections Trail: East African Roads Lead To Nairobi Anew - Francis, Luangisa (Journal of Public Policy and Administration, 2023)
Purpose: Elections in Kenya since 1992 have had an uneven experience with some in which the results were contested only in the end to be accepted by the citizens on the one hand. On the other, in some elections there were crises but which resulted in a workable democratic compromise. This time around, in 2022, Kenya's Supreme Court confirmed William Ruto winner of the country's 2022 disputed national vote and the gesture did not put an end to political instability. The Opposition, Azimio coalition, continued to take the government head on over the high cost of living, issues of constitutional review, the appointment of a new electoral agency commission and the buying off of opposition members of parliament, among others. After two weeks of street protests by the Opposition and in an unexpected turn of events, Ruto (the sitting President) extended an offer of peace calling for dialogue. This study examines whether what is unfolding is yet another reason to believe that Kenya is setting a model for democracy in the East African region bedeviled with some election democracy troubled spots. Methodology: To attain up-to-date and reliable information, engagements have been done in debates, discussions and interviews with personnel who have had different roles and mandates at the level of intervention in the electoral process such as observing, monitoring and supervising; political analysts, political scientists, ruling party personnel, main opposition party personnel and civic educators in the office of the Registrar of Political Parties. Complementing were media tools in its various forms: tabloids (daily or weekly), newsreels, electronic media and others. Findings: Preliminary results from such avenues portray that in what appears as ceding ground from hard stance earlier adopted by the government, the reconciliatory tone stuck by the President is a step going along way to cool down the temperatures that have characterized the country's political space over the last few months. In a similar vein, the gesture by the Opposition to give dialogue a chance is a window of opportunity to get the country back in the course of stability. Unique Contribution to Theory, Practice and Policy: While it remains to be seen how the talks between the two sides will progress, it also remains to be seen as to whether the jargon defining the process, "˜bi-partisan' differs from other wordings like cooperation, grand-coalition, and handshake earlier applied when such situations determined the then defining political atmosphere.